Numerical simulation of blood flow dynamics in a stenosed artery enhanced by copper and alumina nanoparticles - Zainal, Nurul Amira; Zuberi, Haris Alam; Lal, Madan; Singh, Amol; Chamkha, Ali J. (Tech Science Press, 2025)
Nanotechnology holds immense importance in the biomedical field due to its ability to revolutionize healthcare on a molecular scale. Motivated by the imperative of enhancing patient outcomes, a comprehensive numerical simulation study on the dynamics of blood flow in a stenosed artery, focusing on the effects of copper and alumina nanoparticles, is conducted. The study employs a 2-dimensional Newtonian blood flow model infused with copper and alumina nanoparticles, considering the influence of a magnetic field, thermal radiation, and various flow parameters. The governing differential equations are first non-dimensionalized to facilitate analysis and subsequently solved using the 4th order collocation method, bvp4c module in MATLAB. This approach obtains velocity and temperature profiles, revealing the impact of relevant parameters crucial in the biomedical field. The findings of this study underscore the significance of understanding blood flow dynamics in stenosed arteries and the potential benefits of utilizing copper and alumina nanoparticles in treatment strategies. The incorporation of nanoparticles introduces novel avenues for enhancing therapeutic interventions, particularly in mitigating the effects of stenosis. The elucidation of velocity and temperature profiles provides valuable insights into the behavior of blood flow under different conditions, thereby informing the development of targeted biomedical applications. The arterial curvature flow parameter influences temperature profiles, with increased parameters promoting more efficient heat dissipation. The elevated values of Prandtl number and thermal radiation parameter showcase the diminished temperature profiles, indicating stronger dominance of momentum diffusion over thermal diffusion and radiative heat transfer mechanism. Sensitivity analysis of the pertinent physical parameters reveals that the Prandtl number has the most significant impact on blood flow dynamics. A statistical analysis of the present results and existing literature has also been included in the study. Overall, this research contributes to advancing our understanding of vascular health and lays the groundwork for innovative approaches in stenosis treatment and related biomedical fields.